Lost Pathways of Urban Development - Erik Harms (EchoGéo)
Photographic images from Ho Chi Minh City’s Thủ Thiêm Peninsula draw attention to now-vanished trees and pathways from a place that has been demolished for the sake of urban expansion. The trees and pathways in these photographs evoke an aspect of sociality often overlooked in the logocentric anthropological and geographical literature on development-induced evictions. Attention to images draws attention to the history of non-human nature and to lost pathways of urban development, which in turn emphasizes their uses and the practices which maintained them, revealing the interconnection between human sociality and the non-human world. Unlike the "tragedy of the commons," which describes common resources extinguished or depleted by unregulated use, these elements appear as a collective resource, produced and cared for by their users. Reflecting on photographic images taken before and during a period of mass eviction inspires a rethinking of the idea of the commons, crafted through a cultural approach that attends to the material landscape, the role of the non-human in social relationships, and the social production of landscapes.